Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
9514 1404 393
Answer:
- common ratio: -2
- first term -3/4
- sum of 11 terms: -2049/4
Step-by-step explanation:
The formula for the generic term can be solved to find the first term and the common ratio.
an = a1·r^(n-1)
For the given terms, we have ...
a4 = 6 = a1·r^(4 -1)
a7 = -48 = a1·r^(7-1)
Dividing the second equation by the first gives ...
a7/a4 = -48/6 = r^(6 -3)
r = (-8)^(1/3)
r = -2 . . . . . . . . . . the common ratio
Then the first term is ...
6 = a1·(-2)^(3) = -8a1
-6/8 = a1 = -3/4 . . . . . the first term
__
The sum of N terms is ...
Sn = a1·(r^n -1)/(r -1)
Then the sum of 11 terms is ...
S11 = (-3/4)((-2)^11 -1)/(-2-1) = (-1/4)(2^11 +1)
S11 = -2049/4 . . . . . the sum of 11 terms
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.